MONITORING RESPONSE AND OPTIMIZATION OF STUNTING PREVENTION POLICIES IN THE FRONTIER, OUTERMOST, AND DISADVANTAGED AREAS - Asriani , Asriani; Putrawan, Agus; Oktaviani, Venia (MEDIKORA, 2025)
Stunting in disadvantaged, frontier and outermost (3T) areas remains a serious challenge due to limited monitoring of the satisfaction of beneficiaries of multidimensional prevention programs. This study aims to develop a PRO-STUNT 3T model with a multidimensional model (socio-economic, cultural, educational, and health aspects to optimize stunting prevention policies. The specific objectives are to assess the level of beneficiary satisfaction and analyze the factors that influence it in Konawe Regency, Southeast Sulawesi. The research method used a mixed-method approach with a sample of 100 respondents selected through stratified consecutive random sampling from five health centers, the quantitative results were then studied in more depth to enrich the qualitative context. The results showed that 99% of beneficiaries were satisfied with the program, but 8–14% highlighted the limitations of physical facilities (tangibles) and empathy of officers, as well as the dominance of participation by mothers with junior high school education (78%) which has the potential to hinder nutritional literacy. Other findings revealed the program's focus on First 1,000 Days of Life (36% of children aged 0–12 months) but ignored the age group >60 months (4%) who are vulnerable to long-term impacts. Longitudinal studies are needed to evaluate the relationship between community satisfaction and reduced stunting prevalence in the 3T area.